Parental Satisfaction with Care and Support in Neonatal Care Units of Public Hospitals of Nepal - Shrestha, Tumla; Pandey Bista, Archana; Shrestha, Sarala (Journal of Nepal Paediatric Society, 2022)
Introduction: Parental satisfaction is one of the indicators of quality care. An understanding of the satisfying areas would help to identify and prioritize care and support areas for infants and parents. Therefore, this study was conducted to find out the parental satisfaction with care and support in neonatal care units (NCUs). Methods: Cross-sectional descriptive study was conducted in NCUs of five selected public hospitals. The study was conducted among 305 parents of preterm infants (PTIs). After obtaining ethical approval, in-person interviews were conducted with parents using a satisfaction questionnaire. Both descriptive and inferential statistics were used for data analysis. Results: Parents were moderately satisfied with care and support with a median score and interquartile range of 3.4 (3.1- 3.8). They were highly satisfied with the infant care and least satisfied with the attachment and care guidance support with median scores of 4.0 (3.5 - 4.0) and 3.1 (2.6 - 3.8) respectively. Parental satisfaction was significantly associated with parental age, gestational age at birth, and birth weight (P value < 0.05). Conclusions: Parents are moderately satisfied with the care and support received in the NCUs. Their satisfaction is lower with the support for attachment and care guidance. In addition to competent and affectionate care to PTIs, parental support for attachment, guidance, and involvement in care need to be considered by NCU personnel.